An android smartphone-based randomized intervention improves the quality of life in patients with type 2 diabetes in Mysore, Karnataka, India. Issue 5 (September 2020) - Sunil Kumar, D.; Prakash, B.; Subhash Chandra, B.J.; Kadkol, Padma Shrinivas; Arun, Vanishri; Thomas, Jose Jom
Abstract: Background and aims: Associated with severe complications and morbidity, Diabetes Mellitus is a significant public health burden. The need for regular monitoring and adherence to treatment and lifestyle changes have a high impact on the quality of life of the patients. This study attempts to assess the effect of smartphone-based lifestyle modification intervention in the quality of life of patients with type 2 Diabetes through a randomized filed trial. Methods: A randomized field trial was performed among the patients attending the outpatient department of a tertiary care hospital in Mysuru city. A mobile application named DIAGURU, mainly focusing on the lifestyle modification and medication management was used for a period of 6 months from April 2019 to September 2019 by 150 patients in the intervention group while another 150 participants served as controls. The quality of life was assessed using the WHO QOL BREF questionnaire at the beginning of the study and after six months. Results: The change in the quality of life in a positive direction was significantly higher in the intervention group compared to the non-intervention group after six months. The differences in the change in scores of quality of life of participants recruited in intervention and non-intervention groups were statistically significant in all the four domains after the intervention with a p value < 0.001. Conclusion: The evidence generated in this study suggest that such technological approaches can be used as a public health measure to improve the quality of life of patients with type 2 Diabetes Mellitus. Highlights: Reveals the effect a smartphone-based intervention on the quality of life of type 2 diabetes patients in Mysuru. The quality of life was assessed before and after a six month intervention period. The randomized field trial showed that the quality of life improved more in those receiving the intervention.